Edukasi Pengembangan Potensi Peluang Bisnis Berkelanjutan di Bank Sampah Benda Baru Pamulang - Bunga Anisah Harared; Agustina Riyanti; Nabillah Faras Luthfi; Murdhaningsih - (Jurnal Karya untuk Masyarakat (JKuM), 2025)
The waste problem is a pressing global issue because it has a significant impact on the environment. Waste banks are present as an innovative solution in waste management through a waste savings system that involves the community. However, the effectiveness of waste bank management is often constrained by a lack of knowledge and active participation from the community. This article discusses community service activities that aim to increase awareness of waste management and identify sustainable business potential at the Benda Baru Pamulang Waste Bank. The method of implementing the activity includes a needs survey, preparation of socialization materials, implementation of participatory education, and evaluation of program success. The activity was carried out through counseling on the basic concepts of waste management, sustainable business opportunities, and the use of technology in the recycling process. The results of the activity showed an increase in participants' understanding of waste sorting (70.83% to 84.77%) and sustainable business knowledge (48.17% to 74.15%). However, limited time, human resources, and technology are challenges for the implementation of independent recycling practices. This activity emphasizes that sustainable education is needed to encourage more effective and economically valuable waste management. Waste banks have the potential to develop as independent business entities through recycled product innovations, such as handicrafts and eco-enzyme initiatives. The sustainability of the program requires technological support and training to improve operational efficiency and product quality. This initiative is expected to not only increase environmental awareness, but also build entrepreneurial character for waste bank managers and customers.